Analysis of transient using homomorphic deconvolution technique - Salami, Momoh Jimoh Eyiomika; Khalifa, Othman Omran; Jibia, Abdussamad Umar (2010)
Transient multiexponential signals with real decay constants occurs in different areas of science and technology. Such signals arise in deep-level transient spectroscopy, fluorescence decay analysis, NMR relaxation data, etc. Due to their nonorthogonality, their analysis has proved difficult using conventional signal processing techniques. Many techniques have been proposed by different researchers but they often produce mixed result. A new method of multiexponential transient signal analysis is hereby proposed and tested. The method based on cepstral deconvolution is fast and computationally inexpensive. The multiexponential signal is initially converted to a deconvolution model using Gardner transform after which the proposed method is used to deconvolve the data. Simulation and experimental results indicate that this method is good for determining the number of components but performs poorly in estimating the decay rates.